2020
DOI: 10.1016/j.antiviral.2020.104857
|View full text |Cite
|
Sign up to set email alerts
|

A library of nucleotide analogues terminate RNA synthesis catalyzed by polymerases of coronaviruses that cause SARS and COVID-19

Abstract: SARS-CoV-2, a member of the coronavirus family, is responsible for the current COVID-19 worldwide pandemic. We previously demonstrated that five nucleotide analogues inhibit the SARS-CoV-2 RNA-dependent RNA polymerase (RdRp), including the active triphosphate forms of Sofosbuvir, Alovudine, Zidovudine, Tenofovir alafenamide and Emtricitabine. We report here the evaluation of a library of nucleoside triphosphate analogues with a variety of structural and chemical features as inhibitors of the RdRps of SARS-CoV … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
134
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(149 citation statements)
references
References 45 publications
10
134
0
1
Order By: Relevance
“… 11 We also demonstrated that a library of additional nucleotide analogues terminate RNA synthesis catalyzed by the SARS-CoV-2 RdRp. 18 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 We also demonstrated that a library of additional nucleotide analogues terminate RNA synthesis catalyzed by the SARS-CoV-2 RdRp. 18 …”
Section: Introductionmentioning
confidence: 99%
“… 29 , 30 We previously studied Car-TP as an inhibitor of the SARS-CoV and SARS-CoV-2 RdRp using a higher concentration than in the current study. 18 …”
Section: Introductionmentioning
confidence: 99%
“…Potential inhibitors have been investigated to target various steps in the Coronavirus infectious cycle, including the viral replication machinery. 10 However, as of now, no effective therapeutic is available to treat serious coronavirus infections such as COVID- 19. The RdRp is one of the key targets for antiviral drug development.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 We also reported that a library of additional nucleotide analogues with a variety of structural and chemical features terminate RNA synthesis catalyzed by polymerases of coronaviruses that cause SARS and COVID-19. 19 Gordon et al performed a kinetic study, including the determination of Km values for triphosphates of Remdesivir, Sofosbuvir and other nucleotide analogues. 20 Jácome et al recently recommended Sofosbuvir as a possible antiviral for COVID-19, based on structural studies and bioinformatic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Favipiravir (also called avifavir), used in Hepatitis C Virus (HCV) treatment, are also promising drugs [93]. Nevertheless, other antivirals, such as sofosbuvir, alovudine, tenofovir alafenamide, AZT, abacavir, lamivudine, emtricitabine, carbovir, ganciclovir, stavudine, and entecavir, are incorporated by SARS-CoV-2 RdRp and block replication in vitro [95,96]. Another type of broad spectrum ribonucleoside analog, β-D-N4-hydroxycytidine (EIDD-1931), has been shown to inhibit SARS-CoV-2, SARS-CoV and MERS-CoV in cell culture, by increasing the mutation transition rate, probably exceeding the proofreading ability granted by ExoN [97].…”
Section: Introductionmentioning
confidence: 99%